Perilaku Konsumen di Tengah Pandemi COVID-19 - Ali Sadikin; Widiawati, Widiawati (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2022)
Consumer behavior is the study of how individuals, groups, and organizations select, purchase, use, and use goods, services, ideas, or experiences to satisfy their needs and wants. In Islamic economics, the goal of consumption is to maximize maslahah. Maslahah includes the integration of physical benefits and elements of blessing. In consumption, Islam positions it as part of economic activity that aims to collect rewards towards falah (happiness in the world and the hereafter). The motive for consumption in Islam is basically maslahah (public interest or general human good) for needs and obligations. In Islam, consumption cannot be separated from the role of faith. The role of faith is an important benchmark because faith provides a perspective that tends to influence human behavior and personality. Therefore, consumption is important because it fulfills the needs of human life. Without consumption, humans will not survive. What's more, consumption during the COVID-19 pandemic is in violation of the rules and other consumer rights.